Animating the classroom: Pedagogical responses to internationalisation. Issue 3 (July 2016) - Mangan, Anita; Kelemen, Mihaela; Moffat, Sue
Internationalisation of the postgraduate classroom has become a feature of UK business schools, but traditional seminar-led learning often does not suit international students' learning needs. This article reports on a pilot project that used experiential drama workshops, held in a local theatre, as a response to the challenges created by internationalisation. As part of a collaborative auto-ethnography between two academics and a theatre practitioner, the article focuses on a theatre workshop where UK and Chinese MA Management students (the latter being the majority) were given full creative control to create a theatrical performance about the collapse of Enron. We outline how the project provided students with an opportunity to learn about ethical leadership through a series of experiential drama exercises and how it equipped the lecturers with tools and understandings that were subsequently used to teach leadership and critical management studies in a more inclusive way. We conclude by discussing the benefits of using drama techniques to address internationalisation challenges and urge business schools with a large international cohort to engage in a degree of pedagogical risk-taking in order to foster alternative ways of learning that are more inclusive and experientially based.